The Influence of Competence, Training and Work Discipline on Employee Performance of PT. Pos Indonesia (Persero), Binjai Branch Essay 2021 - Eva Dearny; Sonia Chrystabella Hetharie (Jurnal Mantik, 2021)
Does competency affect the performance of employees of PT. Pos Indonesia (Persero) Binjai Branch, Does training affect the performance of the employees of PT. Pos Indonesia (Persero) Binjai Branch, Does work discipline affect the performance of employees of PT. Pos Indonesia (Persero) Cabang Binjai and whether the competence, training and work discipline affect the performance of employees of PT. Pos Indonesia (Persero), Binjai Branch. The population in this study were employees of PT. Pos Indonesia (Persero) Cabang Binjai as many as 75 employees, and the research sample was 57 employees using the entire population. The research model technique uses Multiple Linear Regression Analysis, with data analysis techniques in the form of classical assumption tests, coefficient of determination and research hypothesis testing (simultaneous and partial). The results showed that there was a significant and positive influence of competency variables on the employee performance variables of PT. Pos Indonesia (Persero) Cabang Binjai, there is a significant and positive influence of training variables on the employee performance variables of PT. Pos Indonesia (Persero) Binjai Branch, there is a significant and positive influence of work discipline variables on employee performance variables of PT. Pos Indonesia (Persero) Binjai Branch, tests conducted simultaneously showed that the variables of competence, training and work discipline had a significant effect on the performance of employees of PT. Pos Indonesia (Persero), Binjai Branch. R Square is 0.548 or 54.8%, which means that the influence of competence, training and work discipline on employee performance is 54.8%, while the remaining 45.